Design Web Application Prototype for The Billboard Business on Tuk-Tuk: Case Study of Thai Fan Club on Artists Preference for Thai and Korean Idol Performers - Siriphan, Ratchaya; Phanthabutr, Saowaluck (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
This study is a research and development project that aims to study advertising business on the Tuk-Tuk and to design a prototype of web applications for billboards on the tuk-tuk. The samples of 100 Thai fans of Thai and Korean artists were specifically selected. The research methods used were; 1) Conducting business research on advertising on Tuk-Tuk 2) Exploring the needs and opinions about advertising on Tuk-Tuk 3) Conducting an in-depth interview with samples who have previously advertised on Tuk-Tuk 4) Creating a web application prototype 5) Evaluating web application design prototypes by experts 6) Improving the design of the web application prototype. The quality of instruments was inspected by 7 experts and the data were analyzed by using descriptive statistics. The results of this study shown that the majority of advertising on tuk-tuk customers was a group of artist fan clubs between the ages of 22 and 30 years (80 percent) who were interested in web advertising applications on tuk-tuk because advertising costs were cheap. The problems encountered in dealing with advertising through tuk-tuk were; there was no platform to take care of it specifically, there was only publicity on Twitter, Facebook or Line. The results shown that the prototype design requirements of the web application for the advertising business on a tuk-tuk were to be done under conditions which were: 1. Billboard size; 2. Billboard material; 3. The number of billboards to be produced; 4. The period of time to publicize a billboard; 5. Specifying the start date and end date of the advertising billboard; 6. The tuk-tuk service area; 7. The tuk-tuk service's location, and 8. Returning of the billboard after the contract has expired. The results of the study could be implemented to solve problems found during advertising on tuk-tuks and could also allow the business opportunity of advertising on tuk-tuks to be more efficient.